2004
DOI: 10.1624/105812404x1752
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Experiences of Facilitated Peer Support Groups and Individual Child Health Nursing Support: A Comparative Evaluation

Abstract: The "Early Bird Program" is a support group facilitated by child and family health nurses and offered to families of infants aged 0-8 weeks in South East Sydney, Australia. This paper describes the experiences of 20 women who participated in the Early Bird groups and 20 women who chose to use individual consultations with the child and family health nurse. The qualitative evaluation used focus groups and interviews with the 40 women, and data were analysed using content analysis. Key findings show the Early Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 15 publications
3
30
0
2
Order By: Relevance
“…Common purposes of facilitated groups include providing information, support and fostering interaction for: new parents (Kruske et al . , Guest & Keatinge , Barnes et al . , Schmied et al .…”
Section: Introductionmentioning
confidence: 99%
“…Common purposes of facilitated groups include providing information, support and fostering interaction for: new parents (Kruske et al . , Guest & Keatinge , Barnes et al . , Schmied et al .…”
Section: Introductionmentioning
confidence: 99%
“…This reflects the findings by Barlow and Stewart-Brown (2001) and Kruske et al . (2004) who reported that parents found it more helpful if they were supported in their parenting role rather than being told how to parent. Some PHNs, however, found the experience of delivering a group programme intimidating, and acknowledged the often difficult transition from the role of PHN to facilitator.…”
Section: Discussionmentioning
confidence: 99%
“…El apoyo social que se produce entre las participantes es importante ya que éstas se sienten identificadas con otras personas que se encuentran en su misma situación (5) . Eso hace que la participación de las madres en una dinámica grupal como la descrita puede sea de utilidad al proporcionar apoyo social, influencia en las percepciones de sus capacidades sobre la maternidad, disminuyendo el estrés y la ansiedad y mejorando el afrontamiento de los padres así como el funcionamiento efectivo de la familia (11,12) . El apoyo social que se produce entre las participantes es importante ya que éstas se sienten identificadas con otras personas que se encuentran en su misma situación (5) .…”
Section: Discussionunclassified
“…Esto pone de manifiesto la necesidad del diálogo y de la escucha empática para comprender las preocupaciones y ganar confianza en las capacidades de las madres como cuidadoras (6) . Para finalizar, a pesar de que la evidencia es limitada sobre la manera de fomentar los sentimientos de la madre acerca de sí misma y el apego a su bebé (7) , y de que las intervenciones grupales relacionadas con el cuidado del niño sano no tienen ningún efecto en el sentido de la competencia maternal, la percepción social, el apoyo o el aislamiento, la autoestima, la ansiedad o la depresión en las madres de alto riesgo (12) ; las madres manifiestan una evaluación positiva en la participación de los talleres.…”
Section: Discussionunclassified